Comparative Analysis of G1P[8] Rotaviruses Identified Prior to Vaccine Implementation in Pakistan With Rotarix™ and RotaTeq™ Vaccine Strains - Sadiq, Asma; Bostan, Nazish (Frontiers in Immunology, 2020)
Group A rotavirus (RVA) is the leading cause of severe childhood diarrhea globally, even with all effective interventions, particularly in developing countries. Among the diverse genotypes of RVA, G1P[8] is a common genotype that has continued to pervade around the world, including Pakistan. Two universally accepted rotavirus vaccines-RotarixTM and RotaTeqTM contain the genotype G1P[8]. The current work was aimed at identifying differences between antigenic epitopes of Pakistan's G1P[8] strains and those of the two licensed vaccines. We sequenced 6 G1P[8] rotavirus strains previously reported in Rawalpindi, Islamabad, Pakistan in 2015 and 2016 for their outer capsid genes (VP7 and VP4). Phylogenetic analysis was then conducted in order to classify their specific lineages and to detect their association with strains isolated throughout world. Compared with the RotarixTM and RotaTeqTM vaccine strains (G1-lineage II, P[8]-lineage III), our study G1-lineage I, P[8]-lineage IV strains showed 3 and 5 variations in the VP7 epitopes, respectively, and 13 and 11 variations in the VP4 epitopes, respectively. The G1 lineage II strains showed no single amino acid change compared to RotarixTM (lineage II), but exhibited changes at 2 positions compared to RotaTeqTM (lineage III). So, this has been proposed that these G1 strains exist in our natural setting, or that they may have been introduced in Pakistan from other countries of the world. The distinct P[8]-lineage IV (OP354-like) strains showed twelve and thirteen amino acid variations, with RotarixTM and RotaTeqTM (lineages II and III) strains, respectively. Such findings have shown that the VP4-P[8] component of the G1P[8] strains circulating in Pakistan differs considerably from that of the vaccine viruses compared to that of the VP7-G1. To monitor the long-term effects of vaccines on the emergence of G1P[8] strains with different lineages, routine and successful monitoring of these strains will be crucial.